Sexually Frustrated Mass Shooters: A Study of Perpetrators, Profiles, Behaviors, and Victims - Lankford, Adam (Homicide studies, 2024)
Although several mass killings by incels have received much attention, the overall phenomenon of sexually frustrated offenders seems even larger. This study drew from a recently developed sexual frustration theory to closely examine public mass shooters in the United States from 1966 to 2021 (n = 178). Results showed that some sexually frustrated perpetrators just wanted sex, while others lusted after unavailable partners or had illegal urges that were difficult to satisfy. Quantitative analyses indicated that compared to other mass shooters, sexually frustrated perpetrators were more frequently young, male, unmarried, childless, and unemployed. They were also more likely to be misogynistic, sex offenders, and fame-seekers, and their attacks killed significantly more female victims. Concerted efforts to reduce toxic masculinity and provide better guidance to young men could help reduce this threat.